Code-switching between Cairene mothers and their children in public: - Hussein, Gihan Hamdi (AUC Knowledge Fountain, 2018)

(untitled)
This study investigates the reasons causing a rising number of Cairene mothers to code-switch into English when they speak to their children in public. Further exploration of the mothers’ attitude towards their children’s nascent bilingualism is pursued along with an attempt to identify the mothers’ perspectives on the phenomenon in question when manifested by other parents in their community. To this end, the researcher implemented a mixed methodological approach for data collection starting with a snowball sampling strategy for distribution of a questionnaire, and culminating with a number of follow-up semi-structured interviews of a selected group from the questionnaire participants. Ninety-two participants completed the questionnaire, and eight of them participated in a follow-up interview. Findings of this study show the most prominent reason causing the language behavior of code-switching to spread among Cairene mothers is an attempt to scaffold the child’s linguistic aptitude to prepare them for school. Furthermore, mothers associate fluency in English with a better socio-economic future for their children which justifies their use of English to promote their children’s early bilingualism. However, many of the mothers, despite engaging in this linguistic behavior themselves, have a tendency to perceive the act of code-switching into English in public as intentional to reflect social prestige. The perspectives and attitudes are highly affected by the speakers’ accent, pronunciation, the length of the utterance spoken in English and the context of occurrence. Perspectives are negative when the speakers’ accent and pronunciation are flawed, when the conversation is fully conducted in English or when the context does not require the use of a foreign language.